Bioavailability Enhancement: A Review - HIMANI BAJAJ; SEEMA BISHT; MAYANK YADAV; VINOD SINGH (International Journal of Pharma and Bio Sciences, 2011)
Bioavailability is defined as the rate and extent (amount) of absorption of unchanged drug from its dosage form. It is one of the important parameter to achieve desired concentration of drug in systemic circulation for pharmacological response to be shown. A drug with poor bioavailability is one with poor aqueous solubility, slow dissolution rate in biological fluids, poor stability of dissolved drug at physiological pH, poor permeation through biomembrane, extensive presystemic metabolism. Poorly water soluble drugs often require high doses in order to reach therapeutic plasma concentrations after oral administration. Low aqueous solubility is the major problem encountered with formulation development of new chemical entities. Any drug to be absorbed must be present in the form of an aqueous solution at the site of absorption. This review focuses on the various techniques used for the improvement of the Bioavailability of drugs including size reduction, solubilising excipients, colloidal drug delivery systems, pH adjustment, solid dispersion, complexation, coâ€solvency, micellar solubilisation, hydrotropy etc. The purpose of this review article is to describe the techniques of Bioavailability enhancement for the attainment of effective absorption and improved bioavailability.